Influence of Root Canal Curvature on the Accuracy of Root ZX Electronic Foramen Locator: An In Vitro Study - Saatchi, Masoud; Iravani, Shiva; Akhavan Khaleghi, Mehrdad; Mortaheb, Amin (Iranian Endodontic Journal, 2017)
Introduction: The aim of this in vitro study was to evaluate the correlation between accuracy of Root ZX electronic foramen locator and root canal curvature. Methods and Materials: One hundred and ten extracted mandibular molars were selected. Access cavity was prepared and coronal enlargement of mesiobuccal canal was performed. A #10 Flexofile was inserted into the mesiobuccal canal, and a radiography was taken to measure the degree of curvature by Schneider's method. The actual working length (AWL) was defined by inserting the file until its tip could be observed at a place tangential to the major apical foramen and then 0.5 mm was subtracted from this measurement. For the electronic working length (EWL) measurement, the apical 3 or 4 mm of the root was embedded in alginate as the electrolyte material. The file was inserted into the root canal to the major foramen, until the APEX reading was shown on the electronic device and then pulled back until the visual display showed the 0.5-mm mark. The AWL was subtracted from the EWL to define the distance between the file tip and the point 0.5 mm coronal to the major apical foramen. Data were analyzed using the Pearson’s correlation coefficient. Results: The accuracy of Root ZX within ±0.1 mm and ±0.5 mm was 38.2% and 94.6%, respectively. There was no correlation between the distance from the EWL to the AWL and the degree of root canal curvature (r=0.097, P=0.317). Conclusion: Root canal curvature did not influence the accuracy of Root ZX foramen locator. Keywords: Accuracy; Curved Root Canals; Electronic Apex Locator; Working Length